Pengaruh Model Pembelajaran Kooperatif Tipe Rotating Trio Exchange terhadap Hasil Belajar Kognitif Siswa Kelas VII - Dahliati, Dahliati; Royani, Ida; Safnowandi, Safnowandi (Educatoria : Jurnal Ilmiah Ilmu Pendidikan, 2023)
Based on the results of initial observations at MTs. Nurul Islam Sekarbela Mataram, it was found that student learning outcomes were still relatively low, and the methods used by teachers were still not varied. So the researchers tried to use the rotating trio exchange cooperative learning model. This research was conducted with the aim of knowing the effect of the Rotating Trio Exchange (RTE) cooperative learning model on the cognitive learning outcomes of students at MTs. Nurul Islam Sekarbela Mataram, with one class using the same learning model. This data collection took place from 24 April 2018 to 12 May 2018. In this study there were two types of data obtained, namely, qualitative data and quantitative data on students' cognitive learning outcomes. Meanwhile, quantitative data was obtained from the evaluation results of student learning tests. The data is then analyzed using a predetermined formula. The type of research used is quasi-experimental. The research sample was class VII-B MTs. Nurul Islam Sekarbela Mataram, with a total of 32 subjects. Data collection techniques used observation sheets and questions in the form of essays which totaled 4 questions and multiple choice which totaled 20 questions. The results of this study show that the average value of the pre-test is 47.7 and the post-test is 69.6, so the results obtained in this study have a tcount greater than ttable at a significant level of 5% with dk = 6 (tcount ≥ ttable = 37.380 > 33.362). Thus, it can be concluded that Ha is accepted and Ho is rejected, meaning that there is an effect of using the cooperative learning model of the Rotating Trio Exchange (RTE) type, cognitive biology learning outcomes of MTs. Nurul Islam Sekarbela Mataram academic year 2017/2018.